1983
DOI: 10.1128/jcm.17.6.1127-1131.1983
|View full text |Cite
|
Sign up to set email alerts
|

Detection of group B streptococcal antigens in amniotic fluid of rhesus monkeys

Abstract: To simulate group B streptococci (GBS) amniotic fluid infections common in humans and to examine bacterial growth and the appearance of GBS antigens in vivo, GBS were injected into the amniotic cavity of 19 near-term rhesus monkeys. Transabdominal aspirates of amniotic fluid were obtained before bacterial challenge, after 2 and 6 h, and during cesarean section delivery (24 h). Each fluid was quantitatively cultured for GBS. Specimens of amniotic fluid and gastric aspirate from each infant were tested for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Although similar studies have been published or have appeared as abstracts, the present study utilizes the current modified Directigen reagent and challenges all three products with identical test solutions. Our results comparing the three assays with group-specific antigen in urine and serum are consistent with findings of Hemming et al (9) but different from the findings of Wasilauskas and Hampton (14). The method of preparation of the antigen solutions was not noted in the other investigations comparing the three GBS LPA assays, and thus the limits of sensitivities for the antigen preparations may not be comparable.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Although similar studies have been published or have appeared as abstracts, the present study utilizes the current modified Directigen reagent and challenges all three products with identical test solutions. Our results comparing the three assays with group-specific antigen in urine and serum are consistent with findings of Hemming et al (9) but different from the findings of Wasilauskas and Hampton (14). The method of preparation of the antigen solutions was not noted in the other investigations comparing the three GBS LPA assays, and thus the limits of sensitivities for the antigen preparations may not be comparable.…”
supporting
confidence: 57%
“…Tube dilutions (1:10) were serially made to a concentration of 10-11 g. Streptococcal strains. GBS strains SS878 and Norris (virulent, type III clinical isolates) were prepared as previously described (9). The bacterial concentration was determined spectrophotometrically and then adjusted to a final concentration of 108 bacteria per ml in 0.9% saline.…”
mentioning
confidence: 99%
“…It infection. On the basis of the sensitivity of latex agglutination elevant that the majority of cell-associated type-and reagents used for diagnostic purposes (14), it can be assumed ecific antigens are covalently linked to peptidoglycan that 62 to 83% of neonates with early-or late-onset GBS It is po cally witb may be r group-spx disease have circulating group-specific antigen levels of >125 ng/ml (17).…”
Section: (0) Are Unencapsulated Mutants Of Strains Coh1 (U) Andmentioning
confidence: 99%
“…A variety of methods have been reported to reduce this nonspecific activity in clinical specimens, including heat (1. 6, 7, 13, 16, 23, 24), EDTA (6,7,9,11), N-acetyl-L-cysteine (26), EGTA (12), and dithiothreitol (2, 10, 22). Other investigators have reported the use of either trichloroacetic acid or EDTA to extract bacterial antigens (14,15,18), polyanetholesulfonic acid to precipitate serum protein (20,21), and EDTA to enhance the sensitivity of agglutination reactions (12).…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid and other nonspecific factors have been noted to interfere with LA tests (3,9,12,18,19,25), and several methods have been reported to be helpful in removing interfering factors (6,7). In a previous study, we reported that serum and amniotic fluid could not be used directly with Wellcogen Strep B reagents and that a modification to the method of the manufacturer was necessary (11). We also reported that the use of the serum buffer in the original Bactigen Haemophilus influenzae type b kit did not completely eliminate NSA (L. P. Smith, K. W. Hunter, and G. W. Fischer, Abstr.…”
mentioning
confidence: 99%